LEGAL PROTECTION OF CONSUMERS IN E-COMMERCE TRANSACTIONS: A REVIEW OF CIVIL LAW IN THE DIGITAL ERA - Sanusi Sanusi (Transpublika Publisher, 2024)
In an era of rapid globalization and digitalization, e-commerce has emerged as a cornerstone of the global economy. In Indonesia, e-commerce has experienced tremendous growth. According to data from the Indonesian Ministry of Communication and Information, the value of e-commerce transactions in Indonesia reached Rp 266.3 trillion in 2020 and is expected to continue rising with increased internet and smartphone penetration. Despite the economic benefits, this development has brought forth numerous legal issues that need to be addressed. Consumer legal protection in e-commerce transactions is a crucial issue, considering the prevalence of online fraud, discrepancies in product descriptions, and violations of consumer data privacy. This research explores several significant aspects of consumer legal protection in e-commerce transactions during the digital era, which have not been comprehensively addressed in previous literature. The study adopts a literature review approach to examine this topic, with a focus on civil law in Indonesia. Although the Consumer Protection Law (UU PK) covers various provisions related to the rights and obligations of businesses and consumers in buying and selling transactions, the implementation of the Electronic Information and Transactions Law (UU ITE) in electronic transactions still faces several challenges. Crimes committed by businesses against consumers remain prevalent, and many consumers have yet to receive their rights, especially concerning safety and legal protection when they become victims of breach of contract in electronic transactions.